Sprehod Irene Novak Popov po narečni beneški poeziji - Purič, Vilma (Jezik in slovstvo, 2021)
The article focuses on studies of contemporary poetry from Beneška Slovenija/Slavia Friulana (Venetian Slovenia) by the literary historian Irena Novak Popov. Considering Venetian-Slovenian works as a subsystem within Slovenian literature, Irena Novak Popov recognises its distinct literary form and acknowledges its unique development, which is tied to a specific historical and social framework. She explores this subsystem as a distinct artistic and cultural phenomenon in relation to the mainstream system of Slovenian literature and strives to make the literature of the western edge of the ethnic Slovenian territory more visible in public literary discourse, establishing it as the subject of expert analysis. Through analyses of the individual poetics of a number of authors (Marina Cernetig, Viljem Černo, Aldo Klodič, Gabriella Tomasetig, Andreina Trusgnach and others), she suggests some peculiar components of Venetian-Slovenian writing. The present article highlights the special attitude of Venetian-Slovenian authors towards the local language and their heterogenous presentation of spatial reality.
Keywords: Benečija; jezikovna paradigma; linguistic paradigm; Novak Popov, Irena; predstavnost prostora; Slovenian dialect poetry; Slovenian poetry; slovenska narečna poezija; Slovenska poezija; spatial representation; Venetian Slovenia